VD_FINDINFO AI 514/09 - 186/2011 vom 11. März 2011 - VD Tribunal cantonal (2011)
AIASSURANCE, ADMISSION DE LA DEMANDE, RENTEEN GÉNÉRAL | 60 al. 1 LPGA, 61 let. b LPGA, 61 let. g LPGA, 52 al. 1 LPA-VD, 55 al. 1 LPA-VD